Baffles Shape and Configuration Effect on Performance of Baffled Flocculator - Khudhair, Kifah M.; Eng., Dept. of Civil; Hadi, Duha M. (Basrah Journal for Engineering Sciences, 2019)
Flocculation process is used to agglomerate colloids to form large and heavy flocs. It is accomplished using mechanical or hydraulic slow mixing. The hydraulic mixing is usually achieved using baffles. The aim of this study is to conduct experimental work to study the effect of baffles shape and configuration on baffled flocculator performance. The work includes 304 experiments conducted in a pilot plant of baffled flocculator. Two arrangements of three baffle shapes (blind baffles, baffles of rectangular slot and baffles of circular slots) were adopted. During each experiment, water turbidity and temperature, influent flow rate and head loss were measured. The main outcomes of this study are; (1) for all baffle types and arrangements, flocculation efficiency (FE) increases with the increase of velocity gradient (G) till it reaches a maximum value, then, it decreases and the G value which produces the maximum FE varies with detention time (t), (2) within the applied range of Gt values (10231-25304), the correlation between FE and Gt is weak to moderate positive and varied according to baffles type and arrangement, (3) within the applied range of initial water turbidity (IWT) values (18.1-196) NTU, the correlation between FE and IWT is weak positive to good positive represented by logarithmic relationship, and (4) within the implemented baffle types, the blind baffles type gives the highest FE values for all the baffles number as compared with the other baffle types. Also, the most frequent head loss coefficient values were obtained.